Escherichia coli pathotypes involved in swine colibacillosis: PCR detection, fecal prevalence, and antimicrobial susceptibilities - Kalam, Ramya (Kansas State University, 2023)
Colibacillosis in swine, which includes neonatal enteritis, postweaning diarrhea, and edema disease, is one of the major economically important diseases. The pathotypes of E. coli involved are enterotoxigenic (ETEC), enteropathogenic (EPEC), enteroaggregative (EAEC), and Shigatoxigenic (STEC) E. coli. Our objectives were to determine the effects of in-feed or in- water chlortetracycline (CTC) administration on prevalence of virulence genes and pathotypes implicated in colibacillosis and to compare phenotypic and genotypic susceptibilities to CTC. A total of 1,296 weaned piglets (21 days age) were used in a 35-d study. Piglets were allocated to 48 pens (27 per pen) and pens were assigned randomly to no CTC, in-feed CTC, or in-water CTC groups. The CTC was provided from day 0 to 14. Fecal samples were collected from 5 piglets from each pen on days 0, 14 and 28. Samples were enriched in E. coli broth and subjected to a 11-plex PCR assay to detect major virulence genes targeting the four pathotypes and to a culture method to isolate and identify the pathotypes. Isolates were subjected to the CTC susceptibility testing by micro-broth dilution and major tet genes were determined by PCR. The fecal prevalence of the virulence genes and the pathotypes were not affected by CTC administration (P < 0.05). The predominant enterotoxin genes in pure culture were astA (enteroaggregative heat stable, 29%) and estB (heat stable enterotoxin B; 21.9%). Shiga toxin genes were detected only in day-28 fecal samples and the stx2 gene was more predominant than stx1. The pathotypes of E. coli isolated were ETEC, atypical EPEC (positive for intimin and enterotoxin genes), STEC and ETEC and STEC hybrids. Although the samples were positive for enteroaggregative enterotoxin gene (astA), EAEC pathotype was not detected. All isolates were resistant to CTC and tetA gene (91.5%) was the most predominant. In-feed or in-water CTC administration had no effect on the fecal prevalence of virulence genes and pathotypes implicated in swine colibacillosis and all the tested isolates showed phenotypic and genotypic resistant to CTC.
Keywords: Nursery pigs; Colibacillosis; Escherichia coli pathotypes; In-feed CTC; In-water CTC; Antimicrobial resistance